Towards the integration of markets: Competition in road transportation of perishable goods between Malawi, South Africa, Zambia, and Zimbabwe - Thando Vilakazi; Anthea Paelo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Rapid urbanization and rising income levels in Southern Africa have increased the consumption of perishable and processed food products. This paper relies primarily on firm-level interview data to assess competition and bottlenecks in transporting time-sensitive perishable products across borders between Harare, Johannesburg, Lilongwe, and Lusaka. High transport prices in 2015 - almost double the benchmark rates applied and rates for transportation of commodities - are partly explained by concentration in Malawi, Zambia, and Zimbabwe, and lack of return loads to Johannesburg. Rates could be significantly reduced through a platform for co-ordinating access to return loads, reducing delays at borders, and effectively implementing pre-clearance procedures.
Keywords: D40; F15; L1; L50; L91; L92; 330; road transport; perishable goods; cross-border transport; competition; Southern Africa